Production and purification of chitosanase and Hydrophobins of Lecanicillium lecanii: design of drug nanocarrier delivery system - Hernández Alcántara, Jennyfer (Universidad Autónoma Metropolitana, 2026)
This doctoral research focused on the production, purification, characterization and biotechnological applications of enzymatic and protein systems derived from Lecanicillium lecanii, highlighting their potential in sustainable industrial and biomedical processes. The study was divided into three sections, encompassing the development of chitosanases for chitosan derivatives, the functional production of hydrophobins and their use as biolubricants, and the design of hydrophobin-based nanoparticles for targeted drug delivery. In the first stage, chitosanases were produced through submerged fermentation using chitosan with a degree of acetylation of 18.6% as both the inducer and the sole carbon source. The enzymatic process was optimized in 3 L and subsequently scaled up to a 50 L bioreactor, maintaining operational parameters such as pH, temperature, and oxygen transfer. Purified enzymes displayed molecular weights of 31 and 44 kDa, with optimal activity at 50 °C and pH 6. These chitosanases efficiently hydrolyzed substrates, including acetylated and desacetylated substrates, producing chitooligosaccharides (COS) with a degree of polymerization between 2-6 and low molecular weight chitosan ranging from 8 to 102 kDa. Control of hydrolysis conditions enabled the generation of partially acetylated derivatives at pilot scale, revealing their potential for pharmaceutical, agricultural, and food applications. The second stage focused on the extraction, purification, and functional evaluation of hydrophobins class I and II (8.7 and 5.8 kDa) obtained from L. lecanii cultures grown on chitosan-based media. Both hydrophobins reduced the contact angle on hydrophobic and hidrofilic surfaces. HFBII were used to explore the biomedical potential of hydrophobins class II from L. lecanii as nanocarriers for the anticancer agent pirarubicin (THP). Hydrophobins Class II were structurally characterized by circular dichroism, dynamic light scattering, and electrophoretic analyses to determine their suitability as nanoscale delivery systems. Two nanoparticle formulations were developed: THP-hydrophobin nanoparticles and glucosamine-modified THP–hydrophobin nanoparticles. These nanostructures exhibited mean diameters of 87.43 ± 2.05 nm and 188.30 ± 8.85 nm, respectively, with excellent stability under physiological conditions. In vitro assays using C26 carcinoma cells demonstrated efficient internalization, strong cytotoxicity, and a redox- and pH-responsive release mechanism consistent with the tumor microenvironment. In vivo tests on tumor-bearing mice confirmed selective tumor accumulation, enhanced antitumor efficacy, and reduced systemic toxicity, particularly for the glucosamine-functionalized formulation The third section focuses on emulsions formulated with jatropha oil and hydrophobins I and II, which demonstrated physicochemical stability and tribological properties comparable to the commercial lubricant CIMSTAR-60. Furthermore, microbiological tests revealed a significant decrease in the proliferation of fungal growth (Fusarium, Aspergillus, Cladosporium, and Cephalosporium), supporting their application as eco-friendly, antimicrobial biolubricants for machining processes. Overall, this research demonstrates the remarkable versatility of Lecanicillium lecanii as a biotechnological platform for producing enzymes and surface-active proteins with applications that span from sustainable materials processing to targeted cancer therapy. The chitosanases and hydrophobins characterized herein contribute to advancing environmentally responsible bioprocesses and innovative biomedical solutions.